Translation as ideological practice: Negotiating cultural lexicon from Cantik Itu Luka into al-Jamāl Jarḥ - Retno Nindya Khoirunisa; Akmaliyah; Rohanda (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
The translation of Indonesian literary works into Arabic constitutes a growing yet insufficiently theorized area within cross-cultural literary exchange. While previous studies have examined the Arabic translation of Indonesian novels predominantly through linguistic lenses, no study has systematically analyzed the ideological orientations operative in the translation of cultural lexicon from Indonesian into Arabic. This study investigates domestication and foreignisation strategies in the Arabic translation of Eka Kurniawan's Cantik Itu Luka, rendered as al-Jamāl Jarḥ by Ahmad Syafi'i. Drawing on Venuti's domestication-foreignisation framework and Newmark's cultural lexicon taxonomy, this research employs a qualitative descriptive-comparative method. Data were drawn from the seventh edition of Cantik Itu Luka as the source text and al-Jamāl Jarḥ as the target text, comprising 125 cultural lexical items purposively sampled across five Newmark categories: ecology, material culture, social culture, social organization, and gestures and habits. The findings reveal that domestication predominates, accounting for 65.6% of attested strategies (82 items), while foreignisation accounts for 34.4% (43 items). Domestication prevails in the ecological and gesture categories, whereas foreignisation dominates in social organization through transliteration. These findings demonstrate that the translator's ideological orientation is contextually determined by the degree of cultural specificity embedded in each lexical item, and that foreignisation operates not merely as an ideological choice but as a structural necessity arising from the restricted cultural equivalence between Indonesian and Arabic. This study advances an Arabic-language perspective within the comparative translation scholarship on Cantik Itu Luka translations and extends the applicability of Venuti's framework to a non-European translation context.